2000
DOI: 10.1128/jvi.74.22.10681-10689.2000
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus LMP2A Transforms Epithelial Cells, Inhibits Cell Differentiation, and Activates Akt

Abstract: The Epstein-Barr virus LMP2A protein was expressed in a human keratinocyte cell line, HaCaT, and effects on epithelial cell growth were detected in organotypic raft cultures and in vivo in nude mice. Raft cultures derived from LMP2A-expressing cells were hyperproliferative, and epithelial differentiation was inhibited. The LMP2A-expressing HaCaT cells were able to grow anchorage independently and formed colonies in soft agar. HaCaT cells expressing LMP2A were highly tumorigenic and formed aggressive tumors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
249
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(268 citation statements)
references
References 55 publications
15
249
1
3
Order By: Relevance
“…The exact role of LMP2A inhibition of telomerase activity is still unknown in EBV-associated cell immortalization. The inhibitory effect is consistent with the current view that LMP2A is dispensable in EBVinduced cell immortalization in B cells, but seems contradictory against the notion that LMP2 promotes survival and inhibits apoptosis of Burkitt's lymphoma cells and in gastric carcinoma HSC-39 cell line by a mechanism of inducing Akt phosphorylation and activation [78,79]. It has been speculated that LMP2A inhibits telomerase activity to suppress B-cell activation in order to maintain viral latency [17].…”
Section: Regulation Of Telomerase Activity By the Ebv Proteinssupporting
confidence: 68%
“…The exact role of LMP2A inhibition of telomerase activity is still unknown in EBV-associated cell immortalization. The inhibitory effect is consistent with the current view that LMP2A is dispensable in EBVinduced cell immortalization in B cells, but seems contradictory against the notion that LMP2 promotes survival and inhibits apoptosis of Burkitt's lymphoma cells and in gastric carcinoma HSC-39 cell line by a mechanism of inducing Akt phosphorylation and activation [78,79]. It has been speculated that LMP2A inhibits telomerase activity to suppress B-cell activation in order to maintain viral latency [17].…”
Section: Regulation Of Telomerase Activity By the Ebv Proteinssupporting
confidence: 68%
“…LMP2A and bovine leukemia virus gp 30 were first shown to issue ITAM-dependent signals in T cells (Beaufils et al, 1993). Some functions of the ITAM-containing viral proteins may relate to tumorigenicity, such as survival signalling by activation of the PI3K-Akt pathway by LMP2A and KSHV K1 (Scholle et al, 2000;Swart et al, 2000;Tomlinson and Damania, 2004) and stimulation of cellular migration and invasiveness by LMP2A and MMTV env (Katz et al, 2005;Lu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine residues involved in Shb binding to LMP2A control constitutive Akt activation The LMP2A ITAM tyrosines Y74 and Y85 were previously shown to bind the Syk tyrosine kinase (Longnecker et al, 1991) and mutations of these tyrosines were shown to influence Syk binding to LMP2A as well as LMP2A-mediated Akt activation and survival signalling (Scholle et al, 2000;Swart et al, 2000). Here, we confirm the negative effect of the Y74F and Y85F mutations on the ability of LMP2A to activate Akt (Figure 6, lanes 11 and 12) and extend this observation by showing that the Y64F mutation suppresses Akt activation by LMP2A, either alone (lanes 5 and 6) or in combination with the Y74F mutation (lanes 9 and 10).…”
Section: Downregulation Of Shb Impairs Lmp2a-mediated Akt Activationmentioning
confidence: 99%
See 2 more Smart Citations